ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELANCARAN PENGEMBALIAN KREDIT USAHA RAKYAT (KUR) MIKRO (Studi Kasus pada PT Bank BRI (Persero) Tbk. Unit Tawangsari II, Cabang Sukoharjo Tahun 2013) - Marantika, Carla Rizka; Sampurno, R. Djoko (Diponegoro Journal of Management, 2013)
Kredit Usaha Rakyat is the financing for Micro, Small, Medium Enterprises and Cooperatives (UMKM-K) in the form of giving work capital supported by guarantee facility for productive enterprises. That does not mean if the KUR program has been paid by the government, the program can run smoothly and in accordance with the desired expectations. Of course, various risks began to emerge; one of them is the fluency repay of the Kredit Usaha Rakyat (KUR) by a debtor resulting increased of bank’s NPL if the debtor not smoothly to pay. The aim of this study is to analyze factors that affect fluency repay of KUR Mikro in order to maintain and improve that’s performance.The population in this study are all of KUR Mikro’s debtors at BRI Unit Tawangsari II until January 2013. Sampling method using non-probability sampling with the Slovin calculation. 86 samples was obtained and used in this study, which consists of 43 people representing a smooth to repay loans and 43 represent subpopulations that are not fluent in repay credit. Processing of the data is using qualitative analysis and quantitative analysis using logistic regression.Based on the results of logistic regression analysis for the six independent variables, number of dependents, business experience, and turnover of business have significant effect in the fluency of returning the KUR Mikro but business experience has different direction with hypothesis. While the variables of age, education level, and the loan amount have not significant effect in the fluency of repaying KUR Mikro